Forest of Ilm: A Tawhidic Reflection on Nature and Pharmaceutical Knowledge and Research - Che Mohamad, Che Anuar (Journal of Pharmacy, 2026)
Nature has long served as one of the most fundamental sources of knowledge and guidance for human civilisation, particularly in the field of medicine and pharmacy. Modern pharmacology continues to benefit from natural sources in the discovery and development of therapy. However, contemporary scientific practice often approaches nature through a predominantly utilitarian and reductionist lens, viewing it largely as a reservoir of extractable compounds for new therapy discovery. This article revisits a more holistic framework rooted in Islamic Worldview where nature is understood not only as a material resource, but also as a trust (Amanah) and a source of spiritual and metaphysical knowledge. The article also highlights how principle of Tawhid and moral accountability has shaped earlier scientific inquiry by earlier generation of muslim scientists, particularly in pharmacology and natural product research. Using Forest of Ilm at International Islamic University Malaysia (IIUM) Kuantan as a contemporary case example, the article argues for an integrated approach to scientific research that harmonises empirical investigation with ethical responsibility and spiritual reflection.